Intelligence and Family Size: Another Look - Olneck, Michael R.; Wolfe, Barbara L. (The Review of Economics and Statistics, 1980)
gence on fertility and of household size on offspring's intelligence remain the subject of public debate. Most recently, attention has centered on the decline in Scholastic Aptitude Test scores and the possible effects of the postwar baby boom. These concerns suggest that economists would do well to introduce intelligence into the household utility maximization model used to explain differential fertility. We attempt to do this here.